Hybrid successive discretisation algorithm used to calculate parameters of the photovoltaic cells and panels for existing datasets - Cotfas, Daniel T.; Deaconu, Adrian M.; Cotfas, Petru A. (IET renewable power generation, 2021)
This paper presents a new hybrid successive discretisation algorithm, used to calculate the parameters of the photovoltaic cells and panels, by the one diode model and the two diode model. Nine known datasets from the specialised literature were used to validate the new algorithm and then it was firstly applied for two new datasets. For the first time only one algorithm is applied to extract the parameters, in both cases—one and two diode models. The new datasets are for commercial monocrystalline silicon and amorphous silicon photovoltaic cells. The main test used to prove the performance of HDSA is the root mean square error. Other four tests were used for comparison: the mean absolute error, the mean bias error, t‐statistic, and the coefficient of determination. The hybrid successive discretisation algorithm proved its accuracy and reliability for parameter extraction of different types of photovoltaic cells and panels for all datasets used. Comparing the hybrid successive discretisation algorithm with the best algorithms from the specialised literature shows an improvement of the root mean square error by up to10.4% for the one diode model and by up to 7.5% for the two diode model, respectively.